Pengaruh Radiasi Sinar Gamma Terhadap Pertumbuhan Dan Produksi Bawang Putih (Allium Sativum L) Varietas Kateng - Ningsih, Nina Kurniana (Gema Widyakarya bekerjasama dengan Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
The purpose of this study was to determine the effect of the level of dosage of gamma-ray radiation on the growth and production of varieties of kateng. This research was conducted from August 1999 until December 1999 at Agrayam Experimental Plantation Research Station Bogor. The design of the Randomized Complete Group Design (RKLT) consisted of 6 treatments of gamma-ray radiation dose with 5 replications, in which each replication with the following dosage level A = Control B = 300 Rad, C = 600 Rad, D = 900 Rad, E = 1200 Rad. Each treatment consists of 100 cloves of garlic bulbs grown in one bed. With 10 plant samples. The results showed that the effect gamma-ray radiation on plant height and number of leaves showed a very real effect. Plant height and lowest leaf number is indicated by high dose radiation densities ranging from 1200 rad and 1500 rad. The treatment of gamma ray radiation shows a significant effect on the percentage of live and heavy plants per plot or per hill. Plants are only able to live with a treatment of 600 rad doses while at age 10 MST doses of 900 rad, 1200 rad and 1500 rad of dead plants. The treatment of radiation on root length and dry weight per plot and dry weight per clump has not shown any significant effect, where the plants irradiated below 600 rad are still tolerant given the energies of the environment that allow the garlic plant to survive even though the yield of the bulbs produced is not optimal . This indicates that the radiation This shows that radiation given with strong energy has not been able to result in major fidiological damage. Therefore, the treatment of gamma-ray radiation dose on garlic vraietas Kateng has not been able to show good tuber growth.